Complex comprised of dextran magnetite and conjugated cisplatin exhibiting selective hyperthermic and controlled-release potential - Akinaga Sonoda; Norihisa Nitta; Ayumi Nitta-Seko; et al (International Journal of Nanomedicine, 2010)
Akinaga Sonoda1, Norihisa Nitta1, Ayumi Nitta-Seko1, Shinich Ohta1, Shigeyuki Takamatsu2, Yoshio Ikehata3, Isamu Nagano3, Jun-ichiro Jo4, Yasuhiko Tabata4, Masashi Takahashi1, Osamu Matsui3, Kiyoshi Murata11Department of Radiology, Shiga University of Medical Science, Setatsukinowa-cho, Otsu, Shiga, 520-2192, Japan; 2Department of Radiology, Graduate School of Medical Science, Kanazawa University, Takara-machi 13-1, Kanazawa Ishikawa, 920-8641, Japan; 3Department of Natural Science and Technology, Graduate School of Engineering, Kanazawa University, Kakuma-machi, Kanazawa, Ishikawa 920-1192, Japan; 4Department of Biomaterials, Institute for Frontier Medical Sciences, Kyoto University, Shogoin kawara-machi 53, Sakyo-ku 606-8507, Kyoto, JapanAbstract: We developed a dextran-magnetite conjugated cisplatin (DM-Cis) complex for use in thermal ablation and as a chemotherapeutic drug. To produce DM-Cis we reacted Cis with 1 mL DM (56 mg/mL iron). The temperature rise of DM-Cis was measured in vitro and in vivo under a portable induction-heating (IH) device. Platinum desorption from DM-Cis over 24 hours was measured in bovine serum. In in vivo accumulation and magnet and exothermic experiments we used four rat groups. In group 1 we delivered DM-Cis intraperitoneally (ip) and placed magnets subcutaneously (sc). In group 2 we injected saline (ip) and placed magnets (sc). In group 3 we injected DM-Cis (ip) and placed a sc incision (sham). The control (group 4) received an ip injection of saline. Rectus abdominis muscle tissue was stained with hematoxylin-eosin and iron-stained tissue areas (µm2) were calculated. The maximum platinum concentration in DM-Cis was approximately 105.6 µg/mL. Over 24 hours, 33.48% of platinum from DM-Cis was released. There was a significant difference (P < 0.05) in the iron-stained area between group 1 and the other groups. The temperature in muscle tissue registered a maximum of 56°C after about 4 min. DM-Cis may represent a magnetically-accumulated anticancer drug with hyperthermic effects.Keywords: magnetic nanoparticle-conjugated anticancer agents, DM, portable induction heating device, carboxyl group, rat